Flow over closely packed cubical roughness. (14th June 2021) - Xu, Haosen H.A.; Altland, Samuel J.; Yang, Xiang I.A.; Kunz, Robert F.
Abstract: Abstract : Cube arrays are one of the most extensively studied types of surface roughness, and there has been much research on cubical roughness with low-to-moderate surface coverage densities. In order to help populate the literature of flow over cube arrays with high surface coverage densities, we conduct direct numerical simulations (DNSs) of flow over aligned cube arrays with coverage densities $λ =0.25$ (for validation and comparison purposes), $0.5$, $0.6$, $0.7$, $0.8$ and $0.9$ . The roughness are in the d-type roughness regime. Essential flow quantities, including the mean velocity profiles, Reynolds stresses, dispersive stresses and roughness properties, are reported. Special attention is given to secondary turbulent motions in the roughness sublayer. The spanwise-alternating pattern of the thin slots between two neighbouring cubes gives rise to spanwise-alternating regions of low- and high-momentum pathways above the cube crests. We show that the strength and spanwise location of these low- and high-momentum pathways depend on the surface coverage density, and that the high-momentum pathways are not necessarily located directly above the roughness elements. In order to determine the physical processes responsible for the generation and the destruction of these secondary turbulent motions, we analyse the dispersive kinetic energy (DKE) budget. The data shows that the secondary motions get their energy from the DKE-specific production term and the wake production term, and lose energy to the DKE-specific dissipation term.